Examining Adjacency Pairs in “The Croods: A New Age” Movie: A Conversational Analysis. - Nur Afni Maulidia; Afifah Al Rosyiidah (Journal of Social, Culture, and Language, 2024)
The aims of this study are to explain the types of adjacency pairs and preference structures in the utterances of all the characters in The Croods: A New Age movie. The writers use the theory of adjacency pairs proposed by Yule (1996). This study employs a descriptive qualitative method for data collection. The source of data for this study is the The Croods: A New Age movie, and the data of this study are the utterances of all characters in The Croods: A New Age movie that contain adjacency pairs. The data collection steps are watching the movie, reading the transcription, and selecting and identifying the data. As a result of the study, the writers found 110 instances that consist of types of adjacency pairs and preference structures, which are categorized into preferred and dispreferred responses. In terms of the types of adjacency pairs pattern, there are: greetings with 6 instances, question-answer pairs with 31 instances, offers with 11 instances, requests with 9 instances, invitations with 4 instances, thanking-responses with 2 instances, and assessments with 34 instances. For the preference structure, there are 43 instances categorized as preferred responses and 67 instances categorized as dispreferred responses. Keywords: Adjacency pairs, Dispreferred structure, Preferred structure.